2020
DOI: 10.1111/dom.14176
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre intake in childhood or adolescence and subsequent health outcomes: A systematic review of prospective observational studies

Abstract: Aim: To determine whether higher fibre intakes during childhood or adolescence effect a broad range of intermediate markers of cardiometabolic risk or other health related issues. Materials and Methods: We used online searches up to January 2020 and manual searches to identify prospective observational studies reporting on childhood or adolescent intakes of dietary fibre, vegetables, fruit and refined or whole grains. Outcomes measured later in life were body weight, blood lipids, blood pressure, glycaemia, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 75 publications
(169 reference statements)
0
21
0
Order By: Relevance
“…35 Hence, prospective observational studies are still inconsistent regarding the beneficial role of a fibre-rich diet on adiposity/body weight development during childhood. 11 In our sample, the mean fibre intake at all ages was approximately 17 g/day, which was on average, slightly higher than the European Food Safety Authority (EFSA) adequate intake (AI) for dietary fibre (EFSA AI: 4-6 years = 14 g/day; 7-10 = 16 g/day). 36 One could suggest that we could be measuring a healthier dietary pattern rather than fibre consumption per se; however, our methodological approach showed the independent effect of fibre on each measure of adiposity.…”
Section: Discussionmentioning
confidence: 58%
“…35 Hence, prospective observational studies are still inconsistent regarding the beneficial role of a fibre-rich diet on adiposity/body weight development during childhood. 11 In our sample, the mean fibre intake at all ages was approximately 17 g/day, which was on average, slightly higher than the European Food Safety Authority (EFSA) adequate intake (AI) for dietary fibre (EFSA AI: 4-6 years = 14 g/day; 7-10 = 16 g/day). 36 One could suggest that we could be measuring a healthier dietary pattern rather than fibre consumption per se; however, our methodological approach showed the independent effect of fibre on each measure of adiposity.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, while these studies hint at the important role adequate fiber intake plays in healthy development during childhood, a recent systematic review concluded that low to very low evidence for the relationship between childhood fiber intake and subsequent health outcomes, including cognitive function, is available. 80 A few studies have also investigated the impact of dietary fiber intake in other age groups. In an Australian middle-aged cohort, habitual consumption of higher fiber or multigrain products was associated with better cognitive performance.…”
Section: Evidence From Observational Studiesmentioning
confidence: 99%
“…Additionally, while these studies hint at the important role adequate fiber intake plays in healthy development during childhood, a recent systematic review concluded that low to very low evidence for the relationship between childhood fiber intake and subsequent health outcomes, including cognitive function, is available. 80…”
Section: Dietary Fiber and Cognition: What Do We Know?mentioning
confidence: 99%
“…The healthy effects of fibers were recently analyzed by Reynholds et al, which evaluates 45 observational studies in children aged 1 to 19 years, identifying benefits on body weight, blood lipids, blood pressure, blood glucose associated with an increased intake of fiber with the diet and high-fiber foods, in the absence of adverse events [76]. Positive effects of fiber supplementation on reducing appetite and triglycerides absorption are also demonstrated after a single intake, in the postprandial phase in the obese children [77].…”
Section: Interventions On Specific Aspects Of Dietary Intakementioning
confidence: 99%
“…The intake of fruit, vegetables, and foods rich in fiber has positive effects on various health parameters (satiety, body weight regulation, glycemic control, blood lipids, intestinal microbiota modulation, etc.) [76,81,86]. Therefore, as Pereira-da-Silva concludes in his systematic review on the diet of preschool children, the interventions that determine an improvement in the intake rates of these foods should be implemented and "daily consumption of whole fresh fruit and vegetables should be promoted" [81].…”
Section: From the Age Ofmentioning
confidence: 99%